Islamic finance to meet global ambitions and growth potential The USA Model - kheira ‎ messaoudi; Mohamed Farhi (Dirassat Journal Economic Issue, 2017)
This paper addresses some of the efforts and areas of Islamic finance in some Western countries, where many evidence indicates the increasing opportunities for Islamic finance, especially in the wake of the global financial crisis of 2007, where the recent increase in the interest of many Western countries in Islamic finance, creating opportunities for centers Local and global Islamic finance. After the momentum witnessed by the issuance of financial Shariah compliant by some of these Western countries, the research draws its importance to identify the potential and requirements of the growth of Islamic finance in the United States of America and to strengthen their orientation with such funding, especially in an environment characterized by recognition of traditional funding and non-usury, Such as trade and investment links between the OIC countries - the GCC countries - and Malaysia, increasing investor preference for ethical financial solutions and huge infrastructure requirements to meet future targets As well as government support for the Islamic finance sector from Islamic banking services, products, trade finance and Islamic funds